2020
DOI: 10.1088/1572-9494/ab544b
|View full text |Cite
|
Sign up to set email alerts
|

Weak cosmic censorship conjecture in the nonlinear electrodynamics black hole under the charged scalar field

Abstract: In this paper, we study the thermodynamics and the weak cosmic censorship conjecture of the nonlinear electrodynamics black hole under the scattering of a charged complex scalar field. According to the energy and charge fluxes of the scalar field, the variations of this black hole’s energy and charge can be calculated during an infinitesimal time interval. With scalar field scattering, the variation of the black hole is calculated in the extended and normal phase spaces. In the normal phase space, the cosmolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…After that, many works based on this new experiment [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] show that WCCC is applicable for other kinds of black holes. In addition, more study on the test for WCCC can be found in [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…After that, many works based on this new experiment [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] show that WCCC is applicable for other kinds of black holes. In addition, more study on the test for WCCC can be found in [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%
“…Following Wald various thought experiments were constructed to test the validity of cosmic censorship. These thought experiments involve perturbations of the black holes with both test particles [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24], and fields [25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43]. There were also attempts to incorporate quantum effects [44,45,46,47,48,49,50], and test the validity of cosmic censorship for asymptotically anti-de Sitter cases [51,52,…”
Section: Introductionmentioning
confidence: 99%
“…Following Wald various thought experiments were constructed to test the validity of cosmic censorship. These thought experiments involve perturbations of the black holes with both test particles , and fields [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. There were also attempts to incorporate quantum effects [44][45][46][47][48][49][50], and test the validity of cosmic censorship for asymptotically anti-de Sitter cases [51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%